Metode Pembelajaran Pendidikan Agama Islam Anak Berkebutuhan Khusus Tunanetra SLB A Yaketunis Yogyakarta - Nugroho, Dwi; Astuti, Windi Dwi; Rahmadia, Nurul Anisa; Husna, Difa'ul (Lembaga Yasin AlSys, 2022)
Children with special needs are children who have characteristics that are not the same as children in general. Students who have abnormalities in the eyes are called blind children. Abnormalities in the eyes that cannot see are caused by genetic factors and also accident factors. Blind students in learning need to use assistive devices such as regred and pen for writing Braille letters on paper. Educators in learning need to use different methods from students in general so that it is easily understood by blind children. Islamic religious education needs to be conveyed to blind students so that they have a high spiritual attitude, are able to carry out worship well and also understand the learning material properly and correctly. The learning methods delivered to blind students are lectures, audiotorials, question and answer and practice. This study aims to determine the learning methods of Islamic religious education for blind children at SLB A Yaketunis Yogyakarta. The data collection technique uses a qualitative approach. Qualitative method is a process to find and examine in the research process based on an event. In this study, it examines a variety of fairly complex descriptions and also includes reports from respondents' views directly according to the existing situation. This study uses two types of data, namely primary and secondary data. Which primary data was obtained from respondents directly at the blind inclusion school SLB A Yaketunis Yogyakarta.